Vulnerabilities of Women in Extractive Industries. Issue 1 (June 2017) - Adamson, Rebecca
Perhaps it should not be surprising that sex crimes, the sex trade and anti-woman violence, have become major and predictable by-products of oil, gas and mining extraction operations. After all, mining and drilling camps attract hundreds, even thousands of mostly male workers, typically housed in makeshift 'man camps'. It is a global epidemic. This article looks at the market trends among investors who look at social performance as well as financial performance. It includes a case study on the difference in financial performance between the oil, gas and mining companies that uphold Indigenous peoples' rights and those companies that do not. The results indicate that for the extractive industry and its investors, doing what is right and doing what pays are one and the same when it comes to Indigenous peoples' rights. This article proposes that it would be the same for women's rights and that as governments increasingly prove incapable or unwilling to protect women, we need to turn to the market and make our voices heard. What is needed are the metrics and analytical tools for assessing the impact and financial risks a company can incur, when it fails to recognize women's rights.